# Class 8 RD Sharma Solutions – Chapter 9 Linear Equation In One Variable – Exercise 9.3 | Set 2

### Chapter 9 Linear Equation In One Variable – Exercise 9.3 | Set 1

**Question 13. (7x – 2)/(5x – 1) = (7x + 3)/(5x + 4)**

**Solution:**

Given:

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the

Demo Class for First Step to Coding Course,specificallydesigned for students of class 8 to 12.The students will get to learn more about the world of programming in these

free classeswhich will definitely help them in making a wise career choice in the future.(7x – 2) / (5x – 1) = (7x +3)/(5x + 4)

(7x – 2) / (5x – 1) – (7x +3)/(5x + 4) = 0

By taking LCM as (5x – 1) (5x + 4)

((7x-2) (5x+4) – (7x+3)(5x-1)) / (5x – 1) (5x + 4) = 0

After cross-multiplying we will get,

(7x-2) (5x+4) – (7x+3)(5x-1) = 0

Now after simplification,

35x

^{2}+ 28x – 10x – 8 – 35x^{2}+ 7x – 15x + 3 = 010x – 5 = 0

10x = 5

x = 5/10

x = 1/2

Now verify the given equation by substituting x = 1/2,

(7x – 2) / (5x – 1) = (7x +3)/(5x + 4)

x = 1/2

(7(1/2) – 2) / (5(1/2) – 1) = (7(1/2) + 3) /(5(1/2) + 4)

(7/2 – 2) / (5/2 – 1) = (7/2 + 3) / (5/2 + 4)

((7-4)/2) / ((5-2)/2) = ((7+6)/2) / ((5+8)/2)

(3/2) / (3/2) = (13/2) / (13/2)

1 = 1

Here, L.H.S. = R.H.S.,

Thus the given equation is verified.

**Question 14. ((x+1)/(x+2))**^{2} = (x+2)/(x + 4)

^{2}= (x+2)/(x + 4)

**Solution:**

Given:

((x+1)/(x+2))

^{2}= (x+2) / (x + 4)(x+1)

^{2}/ (x+2)^{2}– (x+2) / (x + 4) = 0By taking LCM as (x+2)

^{2}(x+4)((x+1)

^{2}(x+4) – (x+2) (x+2)^{2}) / (x+2)^{2}(x+4) = 0After cross-multiplying we will get,

(x+1)

^{2}(x+4) – (x+2) (x+2)^{2}= 0Now expand the equation as follows,

(x

^{2}+ 2x + 1) (x + 4) – (x + 2) (x^{2}+ 4x + 4) = 0x

^{3}+ 2x^{2}+ x + 4x^{2}+ 8x + 4 – (x^{3}+ 4x^{2}+ 4x + 2x^{2}+ 8x + 8) = 0x

^{3}+ 2x^{2}+ x + 4x^{2}+ 8x + 4 – x^{3}– 4x^{2}– 4x – 2x^{2}– 8x – 8 = 0-3x – 4 = 0

x = -4/3

Now verify the given equation by substituting x = -4/3,

((x+1)/(x+2))

^{2}= (x+2) / (x + 4)x = -4/3

(x+1)

^{2}/ (x+2)^{2}= (x+2) / (x + 4)(-4/3 + 1)

^{2}/ (-4/3 + 2)^{2}= (-4/3 + 2) / (-4/3 + 4)((-4+3)/3)

^{2}/ ((-4+6)/3)^{2}= ((-4+6)/3) / ((-4+12)/3)(-1/3)

^{2}/ (2/3)^{2}= (2/3) / (8/3)1/9 / 4/9 = 2/3 / 8/3

1/4 = 2/8

1/4 = 1/4

Here, L.H.S. = R.H.S.,

Thus, the given equation is verified.

**Question 15. ((x+1)/(x-4))**^{2} = (x+8)/(x-2)

^{2}= (x+8)/(x-2)

**Solution:**

Given:

((x+1)/(x-4))

^{2}= (x+8)/(x-2)(x+1)

^{2}/ (x-4)^{2}– (x+8) / (x-2) = 0By taking LCM as (x-4)

^{2}(x-2)((x+1)

^{2}(x-2) – (x+8) (x-4)^{2}) / (x-4)^{2}(x-2) = 0After cross-multiplying we will get,

(x+1)

^{2}(x-2) – (x+8) (x-4)^{2}= 0After expansion we get,

(x

^{2}+ 2x + 1) (x-2) – ((x+8) (x^{2}– 8x + 16)) = 0x

^{3}+ 2x^{2}+ x – 2x^{2}– 4x – 2 – (x^{3}– 8x^{2}+ 16x + 8x^{2}– 64x + 128) = 0x

^{3}+ 2x^{2}+ x – 2x^{2}– 4x – 2 – x^{3}+ 8x^{2}– 16x – 8x^{2}+ 64x – 128 = 045x – 130 = 0

x = 130/45

x = 26/9

Now verify the given equation by substituting x = 26/9

((x+1)/(x-4))

^{2}= (x+8)/(x-2)(x+1)

^{2}/ (x-4)^{2}= (x+8) / (x-2)x = 26/9

(26/9 + 1)

^{2}/ (26/9 – 4)^{2}= (26/9 + 8) / (26/9 – 2)((26+9)/9)

^{2}/ ((26-36)/9)^{2}= ((26+72)/9) / ((26-18)/9)(35/9)

^{2}/ (-10/9)^{2}= (98/9) / (8/9)(35/-10)

^{2}= (98/8)(7/2)

^{2}= 49/449/4 = 49/4

Here, L.H.S. = R.H.S.,

Thus, the given equation is verified.

**Question 16. (9x-7)/(3x+5) = (3x-4)/(x+6)**

**Solution:**

Given:

(9x-7)/(3x+5) = (3x-4)/(x+6)

(9x-7)/(3x+5) – (3x-4)/(x+6) = 0

By taking LCM as (3x+5) (x+6)

((9x-7) (x+6) – (3x-4) (3x+5)) / (3x+5) (x+6) = 0

After cross-multiplying we will get,

(9x-7) (x+6) – (3x-4) (3x+5) = 0

Upon expansion we will get,

9x

^{2}+ 54x – 7x – 42 – (9x^{2}+ 15x – 12x – 20) = 044x – 22 = 0

44x = 22

x = 22/44

= 2/4

x = 1/2

Now verify the given equation by substituting x =1/2,

(9x-7)/(3x+5) = (3x-4)/(x+6)

x = 1/2

(9(1/2) – 7) / (3(1/2) + 5) = (3(1/2) – 4) / ((1/2) + 6)

(9/2 – 7) / (3/2 + 5) = (3/2 – 4) / (1/2 + 6)

((9-14)/2) / ((3+10)/2) = ((3-8)/2) / ((1+12)/2)

-5/2 / 13/2 = -5/2 / 13/2

-5/13 = -5/13

Here, L.H.S. = R.H.S.,

Thus, the given equation is verified.

**Question 17. (x+2)/(x+5) = x/(x+6)**

**Solution:**

Given:

(x+2)/(x+5) = x/(x+6)

(x+2)/(x+5) – x/(x+6) = 0

By taking LCM as (x+5) (x+6)

((x+2) (x+6) – x(x+5)) / (x+5) (x+6) = 0

After cross-multiplying we will get,

(x+2) (x+6) – x(x+5) = 0

Upon expansion we will get

x

^{2}+ 8x + 12 – x^{2}– 5x = 03x + 12 = 0

3x = -12

x = -12/3

x = -4

Now verify the given equation by substituting x = -4,

(x+2)/(x+5) = x/(x+6)

x = -4

(-4 + 2) / (-4 + 5) = -4 / (-4 + 6)

-2/1 = -4 / (2)

-2 = -2

Here, L.H.S. = R.H.S.,

Thus, the given equation is verified.

**Question 18. 2x – (7-5x)/9x – (3+4x) = 7/6**

**Solution:**

Given:

2x – (7-5x) / 9x – (3+4x) = 7/6

(2x – 7 + 5x) / (9x – 3 – 4x) = 7/6

(7x – 7) / (5x – 3) = 7/6

After cross-multiplying we will get,

6(7x – 7) = 7(5x – 3)

42x – 42 = 35x – 21

42x – 35x = -21 + 42

7x = 21

x = 21/7

x = 3

Now verify the given equation by substituting

2x – (7-5x) / 9x – (3+4x) = 7/6

(7x – 7) / (5x – 3) = 7/6

x = 3

(7(3) -7) / (5(3) – 3) = 7/6

(21-7) / (15-3) = 7/6

14/12 = 7/6

7/6 = 7/6

Here, L.H.S. = R.H.S.,

Thus, the given equation is verified.

**Question 19. (15(2-x) – 5(x+6))/(1-3x) = 10**

**Solution:**

Given:

15(2-x) – 5(x+6) / (1-3x) = 10

(30-15x) – (5x + 30) / (1-3x) = 10

After cross-multiplying we will get,

(30-15x) – (5x + 30) = 10(1- 3x)

30- 15x – 5x – 30 = 10 – 30x

30- 15x – 5x – 30 + 30x = 10

10x = 10

x = 10/10

x = 1

Now verify the given equation by substituting x =1,

(15(2-x) – 5(x+6)) / (1-3x) = 10

x = 1

(15(2-1) – 5(1+6)) / (1- 3) = 10

(15 – 5(7))/-2 = 10

(15-35)/-2 = 10

-20/-2 = 10

10 = 10

Here, L.H.S. = R.H.S.,

Thus, the given equation is verified.

**Question 20. (x+3)/(x-3) + (x+2)/(x-2) = 2**

**Solution:**

Given:

(x+3)/(x-3) + (x+2)/(x-2) = 2

By taking LCM as (x-3) (x-2)

((x+3)(x-2) + (x+2) (x-3)) / (x-3) (x-2) = 2

After cross-multiplying we will get,

(x+3)(x-2) + (x+2) (x-3) = 2 ((x-3) (x-2))

Upon expansion we will get,

x

^{2}+ 3x – 2x – 6 + x^{2}– 3x + 2x – 6 = 2(x^{2}– 3x – 2x + 6)2x

^{2}– 12 = 2x^{2}– 10x + 122x

^{2}– 2x^{2}+ 10x = 12 + 1210x = 24

x = 24/10

x = 12/5

Now verify the given equation by substituting x = 12/5,

(x+3)/(x-3) + (x+2)/(x-2) = 2

x = 12/5

(12/5 + 3)/(12/5 – 3) + (12/5 + 2)/(12/5 – 2) = 2

((12+15)/5)/((12-15)/5) + ((12+10)/5)/((12-10)/5) = 2

(27/5)/(-3/5) + (22/5)/(2/5) = 2

-27/3 + 22/2 = 2

((-27×2) + (22×3))/6 = 2

(-54 + 66)/6 = 2

12/6 = 2

2 = 2

Here, L.H.S. = R.H.S.,

Thus, the given equation is verified.

**Question 21. ((x+2)(2x-3) – 2x**^{2} + 6)/(x-5) = 2

^{2}+ 6)/(x-5) = 2

**Solution:**

We have,

((x+2) (2x-3) – 2x

^{2}+ 6)/(x-5) = 2After cross-multiplying we will get,

(x+2) (2x-3) – 2x

^{2}+ 6) = 2(x-5)2x

^{2}– 3x + 4x – 6 – 2x^{2}+ 6 = 2x – 10x = 2x – 10

x – 2x = -10

-x = -10

x = 10

Now verify the given equation by substituting x = 10

((x+2) (2x-3) – 2x

^{2}+ 6)/(x-5) = 2x = 10

((10+2) (2(10) – 3) – 2(10)

^{2}+ 6)/ (10-5) = 2(12(17) – 200 + 6)/5 = 2

(204 – 194)/5 = 2

10/5 = 2

2 = 2

Here, L.H.S. = R.H.S.,

Thus, the given equation is verified.

**Question 22. (x**^{2} – (x+1)(x+2))/(5x+1) = 6

^{2}– (x+1)(x+2))/(5x+1) = 6

**Solution:**

Given:

(x

^{2}– (x+1) (x+2))/(5x+1) = 6After cross-multiplying we will get,

(x

^{2}– (x+1) (x+2)) = 6(5x+1)x

^{2}– x^{2 }– 2x – x – 2 = 30x + 6-3x – 2 = 30x + 6

30x + 3x = -2 – 6

33x = -8

x = -8/33

Now verify the given equation by substituting x = -8/33

(x

^{2}– (x+1) (x+2))/(5x+1) = 6x = -8/33

((-8/33)

^{2}– ((-8/33)+1) (-8/33 + 2))/(5(-8/33)+1) = 6(64/1089 – ((-8+33)/33) ((-8+66)/33)) / (-40+33)/33) = 6

(64/1089 – (25/33) (58/33)) / (-7/33) = 6

(64/1089 – 1450/1089) / (-7/33) = 6

((64-1450)/1089 / (-7/33)) = 6

-1386/1089 × 33/-7 = 6

1386 × 33 / 1089 × -7 = 6

6 = 6

Here, L.H.S. = R.H.S.,

Thus, the given equation is verified.

**Question 23. ((2x+3) – (5x-7))/(6x+11) = -8/3**

**Solution:**

Given:

((2x+3) – (5x-7))/(6x+11) = -8/3

After cross-multiplying we will get,

3((2x+3) – (5x-7)) = -8(6x+11)

3(2x + 3 – 5x + 7) = -48x – 88

3(-3x + 10) = -48x – 88

-9x + 30 = -48x – 88

-9x + 48x = -88 – 30

39x = -118

x = -118/39

Now verify the given equation by substituting x = -118/39

((2x+3) – (5x-7))/(6x+11) = -8/3

x = -118/39

((2(-118/39) + 3) – (5(-118/39) – 7)) / (6(-118/39) + 11) = -8/3

((-336/39 + 3) – (-590/39 – 7)) / (-708/39 + 11) = -8/3

(((-336+117)/39) – ((-590-273)/39)) / ((-708+429)/39) = -8/3

(-219+863)/39 / (-279)/39 = -8/3

644/-279 = -8/3

-8/3 = -8/3

Here, L.H.S. = R.H.S.,

Thus, the given equation is verified.

**Question 24. Find the positive value of x for which the given equation is satisfied:**

**(i) (x**^{2} – 9)/(5+x^{2}) = -5/9

^{2}– 9)/(5+x

^{2}) = -5/9

**Solution:**

Given:

(x2 – 9)/(5+x2) = -5/9

After cross-multiplying we will get,

9(x

^{2}– 9) = -5(5+x^{2})9x

^{2 }– 81 = -25 – 5x^{2}9x

^{2}+ 5x^{2}= -25 + 8114x

^{2}= 56x

^{2}= 56/14x

^{2}= 4x = √4

x = 2

**(ii) (y**^{2} + 4)/(3y^{2} + 7) = 1/2

^{2}+ 4)/(3y

^{2}+ 7) = 1/2

**Solution:**

Given:

(y

^{2}+ 4)/(3y^{2}+ 7) = 1/2After cross-multiplying we will get,

2(y

^{2}+ 4) = 1(3y^{2}+ 7)2y

^{2}+ 8 = 3y^{2}+ 73y

^{2}– 2y^{2}= 7 – 8y

^{2}= -1y = √-1

= 1